Improvement in the quality of molecular analysis of EGFR in non-small-cell lung cancer detected by three rounds of external quality assessment. Issue 4 (1st February 2013) - Deans, Zandra C; Bilbe, Neil; O'Sullivan, Brendan; Lazarou, Lazarus P; de Castro, David Gonzalez; Parry, Suzanne; Dodson, Andrew; Taniere, Philippe; Clark, Caroline; Butler, Rachel
Abstract : Background: The clinical need to determine the presence of epidermal growth factor receptor (EGFR) gene mutations in non-small-cell lung cancers (NSCLC) in order to make informed decisions for patient treatment has seen the widespread introduction of EGFR molecular testing in many laboratories. To ensure high-quality molecular testing and allow laboratories to externally measure the standard of the service, an external quality assessment (EQA) scheme was provided to assess the whole testing process. Methods: Formalin-fixed paraffin-embedded NSCLC tumour sections were distributed to laboratories for routine EGFR molecular testing, and the genotyping accuracy, interpretation of the result and clerical accuracy of the report were independently assessed. Results: Three rounds of assessment have identified many genotyping errors and have highlighted the need for external assessment and education in many testing laboratories. The main issues raised were the importance of accurate genotyping, including the use of common mutation nomenclature, clear unambiguous interpretation of the result, the impact of tumour sample assessment regarding amount of tumour being analysed and the heterogeneity of the sample on the molecular test result. Conclusions: Improvements in all these areas were observed during the progression of the three EQA rounds, however, continuous unacceptably high genotyping error rates demonstrate the clear need for continual external assessment and education in this field.